Effect of Compression Loading on Human Nucleus Pulposus-Derived Mesenchymal Stem Cells - Hang Liang; Sheng Chen; Donghua Huang; Xiangyu Deng; Kaige Ma; Zengwu Shao (Stem Cells International)
Purpose. Mechanical loading plays a vital role in the progression of intervertebral disc (IVD) degeneration, but little is known about the effect of compression loading on human nucleus pulposus-derived mesenchymal stem cells (NP-MSCs). Thus, this study is aimed at investigating the effect of compression on the biological behavior of NP-MSCs in vitro. Methods. Human NP-MSCs were isolated from patients undergoing lumbar discectomy for IVD degeneration and were identified by immunophenotypes and multilineage differentiation. Then, cells were cultured in the compression apparatus at 1.0 MPa for different times (0 h, 24 h, 36 h, and 48 h). The viability-, differentiation-, and differentiation-related genes (Runx2, APP, and Col2) and colony formation-, migration-, and stem cell-related proteins (Sox2 and Oct4) were evaluated. Results. The results showed that the isolated cells fulfilled the criteria of MSC stated by the International Society for Cellular Therapy (ISCT). And our results also indicated that compression loading significantly inhibited cell viability, differentiation, colony formation, and migration. Furthermore, gene expression suggested that compression loading could downregulate the expression of stem cell-related proteins and lead to NP-MSC stemness losses. Conclusions. Our results suggested that the biological behavior of NP-MSCs could be inhibited by compression loading and therefore enhanced our understanding on the compression-induced endogenous repair failure of NP-MSCs during IVDD.